Leadership And Decision Making In The Project Management Life Cycle: A Knowledge Management Perspective - Fazaila Shad; Dr. Mehnaz Gul; Dr. Muhammad Zahid (Journal of Business & Tourism, 2021)
All organisations are adopting the project-based approach to carry out operational and business activities. There are many challenges of knowledge management during the project management life cycle because every project has unique characteristics with a changing workforce. Project management involves the leadership and critical decision making which requires the internal and external experts and knowledge. The study is conducted to find out how knowledge management affects leadership and critical decision making in the project management life cycle. The objective of the study is to explore the role of knowledge management in project management and to evaluate the problems of knowledge management in the project management life cycle. In the project management life cycle, much information is generated and experienced. Thus, the study finds out that if the knowledge is not accumulated and recorded correctly, it will be lost and cannot use in future projects. Leadership and critical decision making are affected by knowledge management. Thus, to ensure the best leadership and better decision making there must be proper knowledge management.